Functional and Activation Profiles of Mucosal-Associated Invariant T Cells in Patients With Tuberculosis and HIV in a High Endemic Setting - Balfour, Avuyonke; Schutz, Charlotte; Goliath, Rene; Wilkinson, Katalin A.; Sayed, Sumaya; Sossen, Bianca; Kanyik, Jean-Paul; Ward, Amy; Ndzhukule, Rhandzu; Gela, Anele; Lewinsohn, David M.; Lewinsohn, Deborah A.; et al. (Frontiers in Immunology, 2021)
Background: MAIT cells are non-classically restricted T lymphocytes that recognize and rapidly respond to microbial metabolites or cytokines and have the capacity to kill bacteria-infected cells. Circulating MAIT cell numbers generally decrease in patients with active TB and HIV infection, but findings regarding functional changes differ. Methods: We conducted a cross-sectional study on the effect of HIV, TB and HIV-associated TB (HIV-TB) on MAIT cell frequencies, activation and functional profile in a high TB endemic setting in South Africa. Blood was collected from i) healthy controls (HC, n= 26), 24 of whom had LTBI, ii) individuals with active TB (aTB, n=36), iii) individuals with HIV infection (HIV, n=50), 37 of whom had LTBI, and iv) individuals with HIV-associated TB (HIV-TB, n=26). All TB participants were newly diagnosed and sampled before treatment, additional samples were also collected from 18 participants in the aTB group after 10 weeks of TB treatment. Peripheral blood mononuclear cells (PBMC) stimulated with BCG-expressing GFP (BCG-GFP) and heat-killed (HK) Mycobacterium tuberculosis (M.tb) were analysed using flow cytometry. MAIT cells were defined as CD3+ CD161+ V7.2+ T cells. Results: Circulating MAIT cell frequencies were depleted in individuals with HIV infection (p=0.009). MAIT cells showed reduced CD107a expression in aTB (p=0.006), and reduced IFN expression in aTB (p <0.001) and in HIV-TB (p<0.001) in response to BCG-GFP stimulation. This functional impairment was coupled with a significant increase in activation (defined by HLA-DR expression) in resting MAIT cells from HIV (p<0.001), aTB (p=0.019), and HIV-TB (p=0.005) patients, and higher HLA-DR expression in MAIT cells expressing IFN in aTB (p=0.009) and HIV-TB (p=0.002) after stimulation with BCG-GFP and HK-M.tb. After 10 weeks of TB treatment, there was reversion in the observed functional impairment in total MAIT cells, with increases in CD107a (p=0.020) and IFN (p=0.010) expression. Conclusions: Frequencies and functional profile of MAIT cells in response to mycobacterial stimulation are significantly decreased in HIV infected persons, active TB and HIV-associated TB, with a concomitant increase in MAIT cell activation. These alterations may reduce the capacity of MAIT cells to play a protective role in the immune response to these two pathogens.